2008
DOI: 10.1242/jcs.028217
|View full text |Cite
|
Sign up to set email alerts
|

The JNK-dependent CaMK pathway restrains the reversion of committed cells during osteoclast differentiation

Abstract: and addition of active NFATc1 partially rescued the effect of JNK inhibition. In addition, the level of NFATc1 was decreased by knockdown of CaMK by RNAi and by catalytic inhibition of CaMK, which both caused the reversion of pOCs to macrophages. These data suggest that JNK activity is specifically required for maintaining the committed status during osteoclastogenesis and that the CaMK-NFATc1 pathway is the key element in that specific role of JNK. Supplementary material available online at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 44 publications
1
46
0
1
Order By: Relevance
“…Several intracellular signals are essential for osteoclast formation, including NF-jB, JNK, ERK, and p38 MAPK. JNK activity, in particular, is required to maintain the committed status during osteoclastogenesis (9). We found that ROS mediate LPS-induced osteoclast formation via JNK (Fig.…”
mentioning
confidence: 62%
“…Several intracellular signals are essential for osteoclast formation, including NF-jB, JNK, ERK, and p38 MAPK. JNK activity, in particular, is required to maintain the committed status during osteoclastogenesis (9). We found that ROS mediate LPS-induced osteoclast formation via JNK (Fig.…”
mentioning
confidence: 62%
“…Mouse TLT-1-To discover new molecules that regulate osteoclast differentiation, we monitored gene expression profiles during osteoclast differentiation of human peripheral blood mononuclear cells (18). Microarray analysis revealed that the TLT-1 mRNA level negatively correlated with osteoclastogenesis.…”
Section: Cloning and Characterization Of The Alternative Transcript Ofmentioning
confidence: 99%
“…BMMs (5 3 10 5 cells per well in 6-well plates) were treated with M-CSF (20 ng/ml), RANKL (150 ng/ml), or M-CSF plus RANKL for 6 h. To detect CXCL2, 50 ml of the 1 ml culture supernatant was used for Western blotting (14). After treating BMMs with CXCL2 (50 ng/ml) in the absence or presence of M-CSF (10 ng/ml) for the indicated times, cell lysates were subjected to Western blotting to detect ERK and Akt phosphorylation.…”
Section: Western Blottingmentioning
confidence: 99%